2017
DOI: 10.1186/s40068-017-0100-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of environmental friendly bioinoculate for peanut (Arachis hypogea L.) production in Eastern Ethiopia

Abstract: Background: Bacterial bioinoculate is one of environmentally friendly input for crop production. Several works revealed that effectiveness of Rhizobium bioinoculant have been affected by the native rhizobia population. Hence, this study was initiated to evaluate the effect of selected Bradyrhizobium in nodulating peanut in the major growing areas of Ethiopia. Methods:The effect of eight effective Bradyrhziobium vis-a-vis 20 kg N ha −1 and the control check on the nodulation and yield of two peanut cultivars (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Farmers in the study area reported poor soil fertility as the next yield-limiting factor in groundnut production. Anteneh (2017) reported low soil fertility status as one major abiotic constraint to sustainable groundnut production in the same study areas, which is in agreement with the present study. Groundnut diseases, such as root rot and leaf spot, are among the most important biotic factors that limit groundnut production.…”
Section: Constraints To Groundnut Productionsupporting
confidence: 93%
See 2 more Smart Citations
“…Farmers in the study area reported poor soil fertility as the next yield-limiting factor in groundnut production. Anteneh (2017) reported low soil fertility status as one major abiotic constraint to sustainable groundnut production in the same study areas, which is in agreement with the present study. Groundnut diseases, such as root rot and leaf spot, are among the most important biotic factors that limit groundnut production.…”
Section: Constraints To Groundnut Productionsupporting
confidence: 93%
“…It has a predominantly welldrained sandy loam soil that is ideal for groundnut production. The rainfall distribution of the area is bimodal, with the main rain (locally referred to as Meher rain) received during July to October and short rain (locally known as Belg rain) during March to May (Anteneh 2017). The mean annual maximum and minimum temperatures are 28.1°C and 15.5°C, respectively, with the total annual rainfall ranging from 507 to 984 mm.…”
Section: Description Of the Study Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhizobia may promote plant growth through nitrogen fixation. Anteneh (2017) found that inoculation of Bradyrhizobium is necessary to improve root nodule and seed yields.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, supplementing N fertilizer with biofertilizer such as Rh has been widely proposed, with the aim of increasing the efficiency with which the peanut plant takes up the applied mineral N, as the biofertilizer assists mobilization of soil organic N into plant-available inorganic forms, and also facilitates fixation of atmospheric N within the soil [18]. The legume-Rh symbiosis is one of the most well-known plant microorganism interactions, and accounts for almost 41 kg N ha −1 added into soils annually in peanut cultivation [19]. Argaw [20] reported significant increases in peanut dry matter, nodule number, grain yield and plant N uptake in eastern Ethiopia when N was applied at intermediary rates (20 kg ha −1 ) and combined with Rh inoculation as compared to no N and Rh application.…”
Section: Introductionmentioning
confidence: 99%